ETOS AMERIKA YANG TERCERMIN DALAM NOVEL THE WONDERFUL WIZARD OF OZ KARYA L. FRANK BAUM - SELAH, YUNI PATRISIA; WANTASEN, ISNAWATY L.; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis study aims to describe the values of the American ethos concept in the novel The Wonderful Wizard of Oz written by L. Frank Baum. This study uses the American ethos theory of Herbert McClosky in the book of Traditional Value in American life (1974). The object of this research is the novel The Wonderful Wizard of Oz written by L. Frank Baum, that was downloaded from internet media. The focus of this study is a consept of the American ethos in the novel and classification of the types of characters in the novel. The data collection technique used is a careful reading technique, recording, and interpretation. Two approaches were used, namely intrinsic and extrinsic approaches. The data analysis technique used is descriptive. The results of the study are as follows. (1) Concept of the American ethos in the novel The Wonderful Wizard of Oz written by L. Frank Baum that showing the attitudes, actions, and dialogues of the characters. Therefore, the values of the American ethos concept are found, namely ambition and achievement, profit pursuit and personal interests, as well as competition. (2) The types of characters possessed by the characters namely amoral, expedient, conforming, irrational-conscientious, and rational-altruistic. (3) The types of character reflected in the American ethos, namely amoral, expedient, and rational-altruistic.      Keywords: American Ethos, Types of Character, Values